New wine in old bottles: Modification of the Na + /K + ‐ ATPase enzyme activity assay and its application in salmonid aquaculture - Marius Takvam; Kristina Sundell; Henrik Sundh; Naouel Gharbi; Harald Kryvi; Tom Ole Nilsen (Reviews in Aquaculture, 2024)
The Na + , K + ATPase (NKA) enzyme is important to generate the transmembrane ion gradient in the gills, intestine, and kidneys, hence, is vital for secondary transport of fluids and different solutes in teleosts. Gill NKA enzyme activity is often used as a proxy for parr–smolt transformation (PST) during which anadromous salmonids prepare for seawater (SW). Increased intensification and production of larger smolts in modern salmonid aquaculture has resulted in reports of gill NKA activity being less reliable as a proxy for smolt quality. Consequently, changes in mRNA nka ‐ α1b / α1a ratios in gills are increasingly used as indicators of PST. However, nka isoform mRNA abundance may not reflect translation into the functional protein, nor the activity of the mature enzyme. This may limit the predictive power of molecular markers under certain environmental conditions, rearing regimes and biological scenarios. During PST, the osmoregulatory transformations necessary for SW tolerance and survival does not only occur in the gills. Equally important are the changes in ion transporting activities, including NKA activity, in the intestine and kidneys. However, to our knowledge, there are no previous studies addressing the timing and concurrent changes in NKA activity in the three osmoregulatory tissue during PST. Here we present modifications and optimization of the NKA enzyme activity protocols for gill, intestinal and kidney tissue and outline how to best utilize NKA activity measurements as part of a more holistic approach to evaluate overall smolt quality in modern aquaculture.